A Study on the Challenges Faced By Customers In Financial Inclusion (International Journal of Scientific Research and Management (IJSRM), 2015)
Inclusive growth’ has now become the core agenda of the policymakers across the world. Economic catastrophes in the recent past have proved that for sustainable economic development, the fruits of economic development have to percolate to the bottom of the pyramid. Financial inclusion through banking channels is clearly a critical step in this direction. Indian policymakers have taken many critical initiatives since 2005 to step up financial inclusion in India. All Commercial banks have been working under the directive of the Reserve Bank of India to ensure that every household has access to banking services. Though significant progress has been made, there are many challenges on the way. This study is a critical step in this regard, which aims to identify the key issues faced by the target population in accessing and using financial services. The study is focused on Kerala, which is amongst the top ranked States in India in Financial Inclusion.